2010
DOI: 10.1016/j.ajhg.2010.09.009
|View full text |Cite
|
Sign up to set email alerts
|

Human Male Infertility Associated with Mutations in NR5A1 Encoding Steroidogenic Factor 1

Abstract: One in seven couples worldwide are infertile, and male factor infertility accounts for approximately 30%-50% of these cases. Although many genes are known to be essential for gametogenesis, there are surprisingly few monogenic mutations that have been conclusively demonstrated to cause human spermatogenic failure. A nuclear receptor, NR5A1 (also called steroidogenic factor 1), is a key transcriptional regulator of genes involved in the hypothalamic-pituitary-steroidogenic axis, and it is expressed in the stero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
199
2
7

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 225 publications
(213 citation statements)
references
References 29 publications
5
199
2
7
Order By: Relevance
“…First, interallelic association with the known p.Gly146Ala polymorphism (rs1110061) may further reduce NR5A1 activity and contribute to more severe phenotypes (WuQiang et al, 2003; Hasegawa et al, 2004; Wada et al, 2006; Reuter et al, 2007; Köhler et al, 2008; Lourenço et al, 2009; Bashamboo et al, 2010a; Paris et al, 2011; Camats et al, 2012). However, two patients in our cohort also bore the p.Gly146Ala variant besides the pathogenic NR5A1 variants, p.Trp302Cys and p.Tyr404*, and their phenotype was not strikingly distinct or more severe.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, interallelic association with the known p.Gly146Ala polymorphism (rs1110061) may further reduce NR5A1 activity and contribute to more severe phenotypes (WuQiang et al, 2003; Hasegawa et al, 2004; Wada et al, 2006; Reuter et al, 2007; Köhler et al, 2008; Lourenço et al, 2009; Bashamboo et al, 2010a; Paris et al, 2011; Camats et al, 2012). However, two patients in our cohort also bore the p.Gly146Ala variant besides the pathogenic NR5A1 variants, p.Trp302Cys and p.Tyr404*, and their phenotype was not strikingly distinct or more severe.…”
Section: Discussionmentioning
confidence: 99%
“…Male infertility has been also related to the presence of NR5A1 defects (Bashamboo et al, 2010a; Ferlin et al, 2015). Patients with moderate/severe oligospermia or azoospermia and NR5A1 mutations may have normal testosterone and normal low or low inhibin B levels, but they are at potential risk of deterioration of testicular hormonal secretion with age and may need counseling regarding preservation of sperm and regular monitoring of endocrine function (Bashamboo et al, 2010a).…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8] Although many efforts have been undertaken to identify new causative genes for human male infertility, no candidate gene has been recognised to be administrable in patient care so far. [9][10][11] In contrast, Bashamboo et al 12 found mutations in the NR5A1 gene (MIM 184757) encoding steroidogenic factor 1 (SF1) protein in a substantial fraction of 4% of infertile men (N ¼ 315) with unexplained reduced sperm counts and sperm concentrations below 1 million/ml. All of these were missense mutations leading to reduced protein function in vitro.…”
Section: Introductionmentioning
confidence: 99%
“…All of these were missense mutations leading to reduced protein function in vitro. 12 The SF1 protein has a central role in gonadal development and steroidogenesis, and both male and female Nr5a1 null mice exhibit adrenal agenesis, have female internal genitalia, and gonadal agenesis. 13 Mutations in NR5A1 were first described in patients with primary adrenal insufficiency and 46,XY disorders of sexual development and recently also in women with primary ovarian insufficiency and boys with hypospadias, bilateral anorchia and/or micropenis broadening the phenotypic spectrum.…”
Section: Introductionmentioning
confidence: 99%
“…A significant proportion of male infertility is accompanied by idiopathic azoospermia, most often presenting as non-obstructive azoospermia (NOA), which occurs in B1% of all adult men 3 . A few studies have reported that genetic factors including chromosome number defects, Y-chromosome microdeletions and autosomal mutations or polymorphisms in multiple biological pathways are involved in the development of NOA [4][5][6] .…”
mentioning
confidence: 99%